Hubungan Interaksi Sosial Dengan Hasil Belajar Ilmu Pengetahuan Sosial di SDN Maccini Sombala Makassar - Resky Putri Syam; Suardi Suardi; Syamsuriyanti Syamsuriyanti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
The main problem of lack of social interaction among students is known to be one of the research problems. The research objective was to analyze the relationship between social interaction and social studies learning outcomes at SDN Maccini Sombala. This study uses a mixed strategy (Mixed Methods). The quantitative respondents used a probability sampling of 30 people, while the qualitative used a purposive sampling of 3 people. Data collection techniques are questionnaires, observation, documentation and interviews. The data analysis technique is descriptive statistics. The results of the study show that there is a strong relationship between social interaction and learning outcomes. This can be seen from the results of the measurement of r count which is more prominent than 0.997 ≥ 0.374 or r count ≥ rtable, from the information handling that has been carried out shows that the interaction and learning outcomes at level IV have a strong relationship. The conclusion is that social interaction plays an important role in improving student learning outcomes.